The use of social media as an influence on vaccination rates: A systematic review protocol - Juliana Iscarlaty Freire de Araújo; Francisco de Assis Moura Batista; Marilia Rute De Souto Medeiros; Bárbara de Oliveira Sena; José Adailton da Silva; Fábia Barbosa de Andrade (PLoS ONE, 2025)
Vaccine hesitancy has emerged as one of the major challenges to global public health, exacerbated by the phenomenon of the infodemic—a surge of misinformation amplified through social media platforms. During the COVID-19 pandemic, this dynamic significantly undermined public trust in vaccines. In this context, the present study protocol outlines a systematic review aimed at identifying and synthesizing evidence regarding the influence of infodemia on social media networks and its impact on vaccination coverage. The review will be conducted in accordance with the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis and guided by the PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols) statement. The protocol has been registered in the PROSPERO database (CRD42024581283). The research question was formulated using the PECO framework, where the population of interest is the general public; the intervention is the use of social media; the comparator is non-use of social media or use of other media channels; and the primary outcome is vaccination rates. Both qualitative and quantitative studies with primary or secondary data, published in English, Portuguese, or Spanish, will be included. Searches will be performed across major databases including PubMed, Scopus, Web of Science, Embase, Medline, and Lilacs, as well as gray literature through Google Scholar and OpenGrey. Two independent reviewers will conduct study screening and data extraction using EndNote and Rayyan software. Methodological quality will be assessed using tools such as ROBINS-I and COREQ. This systematic review is expected to contribute evidence to guide health communication strategies, strengthen immunization campaigns, and inform public policies aimed at combating digital misinformation.